2020
DOI: 10.1038/s41419-020-03289-w
|View full text |Cite
|
Sign up to set email alerts
|

Adult mesenchymal stem cell ageing interplays with depressed mitochondrial Ndufs6

Abstract: Mesenchymal stem cell (MSC)-based therapy has emerged as a novel strategy to treat many degenerative diseases. Accumulating evidence shows that the function of MSCs declines with age, thus limiting their regenerative capacity. Nonetheless, the underlying mechanisms that control MSC ageing are not well understood. We show that compared with bone marrow-MSCs (BM-MSCs) isolated from young and aged samples, NADH dehydrogenase (ubiquinone) iron-sulfur protein 6 (Ndufs6) is depressed in aged MSCs. Similar to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Functional and regenerative capacities of MSCs are known to decline with senescence, while the underlying mechanisms that control MSC senescence are not well understood. The work by Zhang et al showed that during the aging process in human and mice, mitochondrial Ndufs6 expression was significantly decreased in aged BMSCs and accelerated BMSC senescence ( Zhang et al, 2020 ). However, based on our microarray results, we did not detect significant depressed expression of mitochondrial Ndufs6 in BMSCs isolated from rats fed with HFD for up-to 12 months ( Supplementary Figure 4A ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional and regenerative capacities of MSCs are known to decline with senescence, while the underlying mechanisms that control MSC senescence are not well understood. The work by Zhang et al showed that during the aging process in human and mice, mitochondrial Ndufs6 expression was significantly decreased in aged BMSCs and accelerated BMSC senescence ( Zhang et al, 2020 ). However, based on our microarray results, we did not detect significant depressed expression of mitochondrial Ndufs6 in BMSCs isolated from rats fed with HFD for up-to 12 months ( Supplementary Figure 4A ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein extracts were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and transferred to polyvinylidene fluoride membranes as previously described [23]. The membranes were incubated with the following antibodies: anti-VEGFA (Proteintech, 66828-1-1 g); anti-pERK1/2 (Cell Signaling, 4370), anti-ERK1/2 (Cell Signaling, 4695), anti-MFN1 (Proteintech, 13798-1-AP), anti-MFN2 (Proteintech, 12186-1-AP), anti-pDRP1 ser616 (Cell Signaling, 3455), anti-DRP1 (Proteintech, 12957-1-AP), and anti-β-actin (Cell Signaling, 3700), at 4°C overnight.…”
Section: Western Blottingmentioning
confidence: 99%
“…In the present study, Wharton's jelly MSC was used because these cells boast enhanced proliferative markers and immunomodulatory capabilities (Kamal and Kassem, 2020). However, the use of Wharton's jelly MSC may also lead to inconsistent results as these postnatal cells are prone to donorspecific variations, such as increased senescence, that can limit its therapeutic efficacy (Zhang et al, 2020a). Using other cell types, such as iPSC-derived MSCs have been shown to have enhanced proliferation as well as safety in human trials (Zhang et al, 2012;Lian and Zhang, 2016;Bloor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%